"USING GAMIFICATION IN EDUCATION AND ENGAGING STUDENTS WITH TECHNOLOGY" (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the concept of gamification in education, highlighting its potential to enhance student engagement and motivation through the integration of game design elements into learning environments. By examining various case studies and research findings, the article demonstrates how gamification can transform traditional educational practices, making learning more interactive and enjoyable. It also discusses the challenges and considerations educators face when implementing gamified strategies and provides practical recommendations for effectively incorporating technology to foster a dynamic learning experience.